ANALISIS KINERJA ORGANISASI BERDASARKAN KRITERIA MALCOLM BALDRIGE DI UNIT RAWAT INAP RSUD EMBUNG FATIMAH BATAM - Heryenzus Heryenzus; Suali Suali (JURNAL AKUNTANSI BARELANG, 2018)
Performance measurement is needed to determine the quality of the hospital. This research aimed to analyze the hospital performance by using Malcolm Baldrige criteria. This research was an observational descriptive study with cross- sectional research design applied. There were 59 nurses and midwives as sample from 143 employees by using simple random sampling. The results of this research showed the performance of Embung Fatimah Batam hospital based on organizational profile (78,82%), customer focus (76,27%), and results criteria (75,59%) were very good. And the hospitalization performance of Embung Fatimah Batam from the leadership criteria (75,81%), strategic planning (75,64%), measurement, analysis, and knowledge management (74,14%), criteria focus of Human Resources (73,74%), and the operations focus (75,00%) were good. When the criterias compared with the maximum value of the Malcolm Baldrige point, included in the category was very good assessment (752,29). Meanwhile the leadership criteria was the highest performance achievements (75,81%), and the lowest was criteria focus of Human Resources (73,34%).It can be inferred that hospitalization of Embung Fatimah Batam performance based on Malcolm Baldrige criteria was very good.